2011
DOI: 10.1088/0004-637x/741/1/17
|View full text |Cite
|
Sign up to set email alerts
|

Where Are the Fossils of the First Galaxies? I. Local Volume Maps and Properties of the Undetected Dwarfs

Abstract: We present a new method for generating initial conditions for ΛCDM N-body simulations which provides the dynamical range necessary to follow the evolution and distribution of the fossils of the first galaxies on Local Volume, 5-10 Mpc, scales. The initial distribution of particles represents the position, velocity, and mass distribution of the dark and luminous halos extracted from pre-reionization simulations. We confirm previous results that ultra-faint dwarfs have properties compatible with being well-prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 97 publications
3
62
0
Order By: Relevance
“…Considering a plausible chemical composition of a first galaxy that may have survived to the present day, Frebel & Bromm (2012) thus argued that Segue 1 (together with Ursa Major II, Coma Berenices, Boötes I, and Leo IV) are candidate systems for such surviving first galaxies. Bovill & Ricotti (2011) agree that most of the ultra-faint dwarfs are consistent with expectations for reionization fossils, although they do not place Segue 1 in this category as a result of earlier estimates of its metallicity lying above the luminosity-metallicity relation established by brighter dwarfs. The metallicities derived in this paper and improved measurements of the L-Z relation by Kirby et al (2013) demonstrate that Segue 1 is in fact consistent with the extrapolated metallicity-luminosity relationship of more luminous systems.…”
Section: The Chemical Evolution Of Dwarf Galaxies and The Milky Waysupporting
confidence: 48%
“…Considering a plausible chemical composition of a first galaxy that may have survived to the present day, Frebel & Bromm (2012) thus argued that Segue 1 (together with Ursa Major II, Coma Berenices, Boötes I, and Leo IV) are candidate systems for such surviving first galaxies. Bovill & Ricotti (2011) agree that most of the ultra-faint dwarfs are consistent with expectations for reionization fossils, although they do not place Segue 1 in this category as a result of earlier estimates of its metallicity lying above the luminosity-metallicity relation established by brighter dwarfs. The metallicities derived in this paper and improved measurements of the L-Z relation by Kirby et al (2013) demonstrate that Segue 1 is in fact consistent with the extrapolated metallicity-luminosity relationship of more luminous systems.…”
Section: The Chemical Evolution Of Dwarf Galaxies and The Milky Waysupporting
confidence: 48%
“…However, as noted in Bland-Hawthorn et al (2014, referred to as Paper I), the timescale for the evaporation of gas is long enough that the star-forming gas in the inner region is protected and can form stars while the gas in the outer regions evaporates. Recent simulations support this view, finding that at least some halos with masses ∼10 7 M can survive the epoch of reionization and continue forming stars (Bovill & Ricotti 2009;Ricotti 2009;Bovill & Ricotti 2011).…”
Section: Introductionmentioning
confidence: 94%
“…These differences are likely due to variations in infall times and environmental processing effects on MW satellite galaxies (e.g., Łokas et al 2012;Rocha et al 2012;Kazantzidis et al 2013). However, others have suggested that reionization can play an increasingly important role in the quenching of star formation in the lowest mass galaxies (e.g., Bullock et al 2000;Ricotti & Gnedin 2005;Bovill & Ricotti 2011aBrown et al 2012;Okamoto et al 2012). We will discuss the topics of reionization (Weisz et al 2014a) and quenching in LG dwarfs in future papers in this series.…”
Section: Trends In Star Formation History As a Function Of Galaxy Stementioning
confidence: 99%